How responsible leadership fosters individual performance: Affective commitment and individual creativity’s sequential mediation - Simões, L. M. (2023)
Research goals and why the work was worth doing : This study sought to answer the question “How employees’ perception of responsible leadership fosters their individual performance?”. It contributes to the literature on responsible leadership (RL), by identifying two mechanisms through which leaders’ behavior fosters employees performance at work, namely affective commitment (AC) and individual creativity (IC).